Cyclic Oxidation Behavior of HVOF Thermally Sprayed WC Cermet Based on AISI 1045 Steel - Muhamad Waldi; Helmi Bagas Samudra; Ahmad Maulana Arkan Leksana; Djoko Hadi Prajitno; Haris Tjahaya (BRIN, 2022)
Thermal spray coating technology High-Velocity Oxygen Fuel (HVOF) has become one of solution for metal protect and parts recondition that work in critical environments such as oxidative, erosive, and corrosive. One of the thermal spray coatings (TSC) application has been carried out to improve the oxidation resistance of the Induce Draft Fan (IDF) as a part on coal fired steam power plant unit. Cermet WC10Co4Cr and WC17Co are intended to sustain the AISI 1045 steel substrate against the oxidative environment. In this works, the cyclic oxidation at a temperature 500oC were conducted to reveal the oxidation resistance behavior of the coatings. Several mechanical tests are also presented including surface roughness of the coatings, coatings microhardness, and coatings adhesion. The coatings morphology was also characterized using SEM microscope, as well as X-ray diffraction (XRD) for phase analysis after the oxidation test. KeywordHVOF, Oxidation resistance, Induce draft fan.